A tributação extrafiscal sobre a taxa de licenciamento ambiental: um estudo de caso de uma empresa de beneficiamento de resíduos sólidos no estado do Amazonas - Silva , Adriana Brito da (2014)
With the increase of environmental degradation on account of the problem of solid waste faced by our society, the environmental Law, economic Law and taxation extrafiscal has shown excellent tools in the establishment of Public Policies aimed at resolving this degradation. A clear example of this is the recent National Policy of Solid Waste (PNRS), established by Law no. 12.305 of August 2010, which determines various actions, both to Public Power as society in general, for the implementation of the management of waste, and is based on environmental principles such as the polluterpays principle and the shield-recipient. The principle of the shield-recipient innovates to allow the granting of incentives to those who protects the environment, as a way to ensure the realization of the PNRS, encouraging the activities focused on the management of waste. In this context, the PNRS brought as one of its objectives the incentive the recycling industry and the institution by can Public standards for granting of incentives both entities as the industries of this branch. On this basis, this work deals with the use of taxation extrafiscal (inducer) on the rate of environmental licensing of companies that operate in the field of processing of solid waste, from a case study conducted in a company in the business of solid waste beneficiation of metallic, located in the State of Amazonas.